2020
DOI: 10.1182/bloodadvances.2020001779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of older patients with AML receiving hypomethylating agents: a large population-based study in the United States

Abstract: The hypomethylating agents (HMAs) azacitidine and decitabine have been the de facto standard of care for patients with acute myeloid leukemia (AML) who are unfit for intensive therapy. Using the Surveillance, Epidemiology, and End Results-Medicare linked database, we identified 2263 older adults (age ≥66 years) diagnosed with AML during 2005-2015 who received a first-line HMA; 1154 (51%) received azacitidine, and 1109 (49%) received decitabine. Median survival from diagnosis was 7.1 and 8.2 months (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 38 publications
(68 reference statements)
5
53
2
2
Order By: Relevance
“…As expected ELN risk group and attainment of CR were key determinants of survival outcomes in our cohort 27 . In comparison, a recent survival analysis from a large population based data‐set including over 2000 AML patients treated with HMA monotherapy demonstrated a median survival of 7 to 8 months 21 . Furthermore, results from the recently completed randomized placebo control trial (VIALE‐A) comparing venetoclax and azacitidine with placebo and azacitidine demonstrated superior complete response rates of 66.4%, with the former regimen vs 28.3% translating to an overall survival benefit with the addition of venetoclax (median survival of 14.7 vs 9.6 months respectively; P < .001) 28 …”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…As expected ELN risk group and attainment of CR were key determinants of survival outcomes in our cohort 27 . In comparison, a recent survival analysis from a large population based data‐set including over 2000 AML patients treated with HMA monotherapy demonstrated a median survival of 7 to 8 months 21 . Furthermore, results from the recently completed randomized placebo control trial (VIALE‐A) comparing venetoclax and azacitidine with placebo and azacitidine demonstrated superior complete response rates of 66.4%, with the former regimen vs 28.3% translating to an overall survival benefit with the addition of venetoclax (median survival of 14.7 vs 9.6 months respectively; P < .001) 28 …”
Section: Discussionsupporting
confidence: 60%
“…Prior to its approval in combination with HMA or low dose cytarabine, therapy was limited to HMA with modest responses, longer time to response and marginal survival benefit. 21 Our observations are reflective of both published clinical trial and "real world" reports with a comprehensive comparison provided in Table S3. 10,24 Low early mortality and infection rates including invasive fungal infections were similar to published clinical trial data.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Hypomethylating agents (HMAs) such as decitabine and azacitidine are DNA methyltransferase (DNMT) inhibitors which alter DNA methylation patterns, leading to increased expression of tumor suppressors and apoptosis [ 63 ]. In adults, these therapies prolong survival but rarely lead to sustained remission when used as a single agent [ 64 ]. Decitabine has also been used as maintenance therapy for adults with AML but did not protect against relapse when used in this setting [ 65 ].…”
Section: New Therapymentioning
confidence: 99%
“…The treatments administered to DLBCL patients were retrieved from the NHIRD with anatomical therapeutic chemical (ATC) codes (https://www.whocc.no/atc_ddd_inde x/). 21 A change in chemotherapy was defined as any adjustment of chemotherapy except for regimen switching between CHOP and CVP or between R-CHOP and R-CVP. Rituximab was administered as a frontline treatment if the interval between the start date of rituximab and that of other chemotherapy agents was less than 42 days.…”
Section: Definition Of Chemotherapies Hbv Infections and Antiviral mentioning
confidence: 99%